Official Institute Reports for the Year 1923 (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1923)
TO THE, BOARD OF DIRECTORS OF THE AMERICAN INSTITUTE OF MINING AND METALLURGICAL ENGINEERS Gentlemen -The following report covers briefly some of the more important activities of the Institute during the year 1923. In my report for the year 1922, I drew attention to the falling off in membership of the Institute due to the depressed condition of the mining industry in several lines and the inability of many of our members to find profitable employment in mining or its associated branches. A number who were unemployed during 1922 established connections during 1923, but a still greater number have been forced to resign or drop their membership during 1923 Fortunately, the number dropped is not so great as in the previous year. The Employment Service conducted by, the four Founder Societies bears witness to the trend in business For the young men just out of college, there are plenty of opportunities at small salaries, there are plenty of opportunities for them as laborers; but for the mature members, those of experience, there are few calls During the last eighteen months, our Employment Service has been able to place only six of our members out of every hundred engineers for whom it has found work. Another loss which this Society has suffered, but which is not felt so keenly by our sister societies, is in its foreign members. The A. I M. E. has always had a large foreign membership, but of recent years exchange has been so heavily against many European and South American coun¬tries that a large number of members residing abroad have been compelled to relinquish their membership Almost invariably these members express keen regret because of the necessity that confronts them, and almost invariably the writers express hope that present conditions will not last long and that they will soon be able to ask for reinstatement. Having stated the darkest side of the picture first, it may now be drawn to your attention that in spite of these losses the number of persons applying for membership was decidedly encouraging. From the quality point of view, the membership has not gone back¬ward The Membership Committee has declined to recommend many